2020
DOI: 10.4315/jfp-19-614
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of Commercially Produced Protective Cultures with Common Cheesemaking Cultures and Their Antagonistic Effect on Foodborne Pathogens

Abstract: The documented survival of pathogenic bacteria, including Listeria monocytogenes (LM), Shiga toxin–producing Escherichia coli (STEC), and Salmonella during the manufacture and aging of some cheeses highlights the need for additional interventions to enhance food safety. Unfortunately, few interventions are compliant with the Standards of Identity for cheese. Protective bacterial cultures (PCs) represent actionable, natural interventions. However, supportive data for commercially produced PCs regarding their ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…L. monocytogenes levels remained the same in these fruit samples stored at 4°C, possibly influenced by competition for nutrients with yeasts and molds. Gramisci et al (2018) and Gensler et al (2020) both demonstrated the antagonistic effect that the growth of yeast and mold can have on foodborne pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…L. monocytogenes levels remained the same in these fruit samples stored at 4°C, possibly influenced by competition for nutrients with yeasts and molds. Gramisci et al (2018) and Gensler et al (2020) both demonstrated the antagonistic effect that the growth of yeast and mold can have on foodborne pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…When the three adjunct cultures were evaluated as a pool, positive results were obtained at 8 and 14 °C mostly due to the presence of Carnobacterium , but also to the synergic effect generated by bacteriocins production by the three bacterial strains. LAB mixed cultures often demonstrated to exert a highest protective action without affecting the cheese making and the final organoleptic properties [ 14 , 15 , 56 ]. As a general observation, the use of adjunct cultures significantly shapes the cheese microbiota, by reducing the alpha-diversity index, as shown in Figure 4 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the metabolic behavior of Lactobacillus spp. in one cheese has been investigated by means of traditional analytical techniques [ 14 ], but no detailed description of the released compounds has been reported while interacting with pathogens [ 16 , 17 , 20 , 22 , 23 , 24 , 25 , 26 ]. Recently, Tzora et al [ 27 ] established differences in the molecular signaling (also called cross-talk) exchanged between resident microbiota in Kefalograviera cheese after the feeding system of the dairy sheep was changed.…”
Section: Introductionmentioning
confidence: 99%